Trends in novel antiandrogen receptor signal inhibitor use and medical costs in prostate cancer - Hikari Miura; Hayato Yamamoto; Yoshiharu Okuyama; Noritaka Ishi; Ryuma Tanaka; Takuya Oishi; Fumiya Yoneyama; Tomoko Hamaya; Kyo Togashi; Naoki Fujita; Teppei Okamoto; Chikara Ohyama; et al. (Cancer Medicine)
Abstract Objective We aimed to examine trends in novel antiandrogen receptor signal inhibitor (ARSI) usage and medical costs by collecting real‐world big data included in The National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB) Open Data, covering most of the clinical practices throughout Japan. Methods Usage data for outpatient prescriptions from 2016 to 2021 were extracted from the NDB Open Data. Among the 459,610 million tablets/capsules prescribed, prostate cancer‐specific agents (bicalutamide, estramustine phosphate, flutamide, abiraterone, enzalutamide, apalutamide, and darolutamide) were selected to investigate the trends of usage and medical costs. Results In total, 764.8 billion medications were recorded. Among these, standard dose‐adjusted prescriptions for bicalutamide, abiraterone, enzalutamide, apalutamide, darolutamide, and other vintages (estramustine phosphate, flutamide) was 276, 14.2, 18.1, 2.19, 0.34, and 20.3 million, respectively. The usage of ARSI increased significantly from 6.1% in 2016 to 16% in 2021. The medical costs for prostate cancer‐specific agents increased significantly (1.8‐fold) from 2016 to 2021. Despite the limited usage of ARSIs, a majority of the medical costs had been spent on ARSIs. Medical costs associated with ARSIs increased significantly from 59% to 89% (p < 0.001). Conclusion ARSI usage and medical costs associated with prostate cancer increased significantly from 2016 to 2021. Despite the limited use of ARSIs, a considerable proportion of the medical costs for prostate cancer‐specific agents had been spent on ARSIs.